2015
DOI: 10.5901/mjss.2015.v6n6s4p549
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Physico-Chemical and Microbiological Quality of Imabolo Stream Water in Ankpa Urban Area of Kogi State, Nigeria

Abstract: The non-functional public water supply in most urban areas has compelled residents to resort to the use of stream water for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 4 publications
5
10
3
Order By: Relevance
“…In conformity to our results, Odikamnoro et al [48] reported a pH value of 7.67 ± 0.06mgL -1 in borehole water samples from Abakaliki capital city. Michael et al [33] reported a ph value of 7.50 ± 0.22 in water samples collected in Ankpa urban area of Kogi State. John [34] reported a mean pH of 8.10 ± 0.10.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In conformity to our results, Odikamnoro et al [48] reported a pH value of 7.67 ± 0.06mgL -1 in borehole water samples from Abakaliki capital city. Michael et al [33] reported a ph value of 7.50 ± 0.22 in water samples collected in Ankpa urban area of Kogi State. John [34] reported a mean pH of 8.10 ± 0.10.…”
Section: Resultsmentioning
confidence: 99%
“…Ndamitso et al [36] in their study reported that chemical oxygen demand in water samples from Minna in Niger State ranged from 104.00 ± 2.00 to 206.53 ± 3.20mg/dm 3 . Michael et al [33] reported an average chemical oxygen demand level of 8.6 ± 2.52mgL -1 in Kogi State. Nwali et al [31] reported that chemical oxygen demand values for freshwater samples ranged from 0.03mgL -1 (Ope-ekwe) to 4.80mgL -1 (Ikwo-ihie).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The WQI from the stations showed that the status water in the stream can be ranked as medium for all the stations except Kogi State College of Education Area and Transportation land-use zones that revealed bad status in terms of water quality categorization during this season. The water quality index among stations was in the pattern S1>S2>S3>S4>S5<S6>S7 which showed the decrease in the quality of water down the stream channel [32]. The decrease in value along stations is a reflection of different types of pollutants entering the stream due to various activities such as discharge of domestic sewage, runoff water from agricultural lands near the banks of the stream (see Table 4).…”
Section: Variation In Microbiological Characteristics Of Imabolo Strementioning
confidence: 98%